ChemInform Abstract: Total Synthesis of (—)‐Stemoamide by Sequential Overman/Claisen Rearrangement. Issue 43 (7th October 2016) - Nakayama, Yasuaki; Maeda, Yuichiro; Hama, Naoto; Sato, Takaaki; Chida, Noritaka
Abstract: The enantioselective total synthesis of (—)‐stemoamide using Overman/Claisen rearrangement of an allylic 1, 2‐diol is reported.